LEXICAL DENSITY OF READING TEXTS IN ENGLISH TEXTBOOK OF JUNIOR HIGH SCHOOL - Desi Ariska; Isli Iriani Indiah Pane (Universitas Negeri Medan, 2016)
This study deals with lexical density of English reading texts in the textbook of junior high school. The objectives of the study are to find out the lexical density of reading texts of English in Focus textbook, the text which has the highest lexical density in the reading texts, and the reason of the text which has the highest lexical density in reading texts. This study was conducted by descriptive qualitative method. The data of this research were the English reading texts of English in Focus textbook for ninth grade students of junior high school published by National Education Department. The result of the analysis showed that: (1) The lexical density of procedure texts are 5.90, 5.08, 5.5, and 4.69, report texts are 5.92, 4.22, 4.06, and 3.64 and narration texts are 2.92 and 2.90. The score showed that the lexical density of eleven reading texts on English in Focus textbook for ninth grade of junior high school is categorized medium based on the Halliday’s theory. It means that the texts are not difficult, easy to understand and suitable for ninth grade students of junior high school. (2) The highest lexical density of the reading texts is report text entitled “The Chinese Influence in Indonesian Visual Art” (5.92) because of the higher number of lexical items than grammatical items, few clauses and more vocabularies of words. (3) Report text has the highest lexical density because of the high proportion of lexical items in the text and it also because of the generic structure, language features and the style of writing report text.